O ESPALHAMENTO NUCLEON-NUCLEON EM ENERGIAS EM ENERGIAS INTERMEDIARIAS: O PAPEL DE PION - Battistel, Orildo Luis (1989)
O ESPALHAMENTO NUCLEON-NUCLEON EM ENERGIAS EM ENERGIAS INTERMEDIARIAS: O PAPEL DE PION